Effect of additional Nordic hamstring exercise or sprint training on the modifiable risk factors of hamstring strain injuries and performance - Ripley, N. J.; Cuthbert, M.; Comfort, P.; McMahon, J. J. (PLOS ONE, 2023)
The Nordic hamstring exercise (NHE) has commonly been investigated in isolation, however, within practice multiple modalities are commonly incorporated. However, the NHE has a low level of compliance within sport, with sprinting being potentially being preferred. The present study aimed to observe the effect of a lower-limb program with either additional NHE or sprinting on the modifiable risk factors hamstring strain injury (HSI) and athletic performance. 38 collegiate athletes were randomly assigned into three groups: control standardised lower-limb training program (n = 10 (2 female, 8 male), age = 23.50 ± 2.95 years, height = 1.75 ± 0.09 m, mass 77.66 ± 11.82 kg), additional NHE (n = 15 (7 female, 8 male), age = 21.40 ± 2.64 years, height = 1.74 ± 0.04 m, mass 76.95 ± 14.20 kg) and additional sprinting (n = 13 (4 female, 9 male), age = 22.15 ± 2.54 years, height = 1.74 ± 0.05 m, mass 70.55 ± 7.84 kg). All participants performed a standardised lower-limb training program twice per week for seven weeks, including Olympic lifting derivatives, squatting movements, and the Romanian deadlift, with experimental groups performing with either additional sprinting or NHE. Bicep femoris architecture, eccentric hamstring strength, jump performance, lower-limb maximal strength and sprint ability were measured pre and post. All training groups demonstrated significant (p < 0.001), small-moderate increases in Bicep femoris architecture (g = 0.60-1.22), with significant (p < 0.001), small-large increases in absolute and relative eccentric peak force (g = 0.60-1.84). Significant and small increases were observed in take-off velocity and mean propulsion force (p < 0.02, g = 0.47-0.64), with non-significant and small increases for both the sprint and control training groups for mean propulsion force (p > 0.05, g = 0.42-0.50). Nordic and sprint training groups had significant and small increases in peak absolute and relative net force (p < 0.001, g = 0.44-0.60). The control group had a non-significant trivial increase in absolute peak net force (p > 0.05, g = 0.22), with a significant and small increase in relative peak relative net force (p = 0.034, g = 0.48). Significant and small decreases for the NHE and sprinting training groups was observed for 0-10 m, 0-20 m, and 10-20 m sprint time (p < 0.010, g = 0.47-0.71). Performing multiple modalities, with either additional NHE or sprinting, as part of a complete resistance training program was superiorly effective for measures of modifiable risk factors HSI, with similar increases observed in measures of athletic performance derived from the standardised lower-limb training program.